Successful use of next generation genomic sequencing (NGS)-directed therapy of clear cell carcinoma of the ovary (CCCO) with trametinib and metformin in a patient with chemotherapy-refractory disease. Issue 1 (May 2015) - Castro, Michael; Whitcomb, Bradford; Zajchowski, Deborah; Coleman, Robert
Abstract Purpose Compared to other subtypes of epithelial ovarian cancer, clear cell carcinoma of the ovary bears an ominous reputation for chemotherapy resistance, increased relapse rate, and diminished survival. Among patients with distinct histopathologic subtypes, molecular analyses have identified a variety of known drivers of the malignant behavior, and depict a striking heterogeneity. Methods A patient with rapidly metastatic CCCO that was refractory to taxane, platinum, pemetrexed, and bevacizumab-based strategies underwent molecular profiling which disclosed dual MAPK and PI3K/AKT/mTOR pathway mutations. Results Combined targeted therapy with trametinib and metformin resulted in a dramatic disease regression without toxicity. Conclusion The case highlights the utility of precision medicine combining individual molecular diagnosis with rational therapeutic intervention with targeted agents.